OPTIMIZATION OF ZAKAT FUND MANAGEMENT, INFAQ AND SHADAQAH IN IMPROVING MUSTAHIQ'S LIFESTYLE AT THE NATIONAL ZAKAT AMIL BODY OF SAMBAS DISTRICT - Agung Prihatin; Sumar’in Sumar’in; Serli Serli (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
The potential of Zakat, Infaq and Sadaqah (ZIS) in Indonesia is very large as an instrument to reduce poverty and improve people's welfare. This study assesses the effectiveness of ZIS management as optimally as possible, so that it can make a significant contribution to reducing poverty and increasing welfare. Law No. 23 of 2011 concerning zakat management has provided a strong legal basis in zakat management, through collection, distribution and utilization. The formulation of the problem in this study are: 1. How to optimize the management of zakat, infaq and shadaqah funds in increasing the standard of living of mustahiq. 2. How to improve the standard of living of mustahiq recipients of productive zakat from Baznas, Sambas Regency. The purpose of this research is to find out how to optimize the management of zakat, infaq and natural shadaqah funds to increase the standard of living of mustahiq. and to determine the level of public trust in the management of Baznas in Sambas Regency and to determine the improvement in the standard of living of mustahiq recipients of productive zakat from Baznas in Sambas Regency. This type of research is a field research conducted at Baznas, Sambas Regency. The nature of this research is descriptive qualitative and data collection techniques are carried out by interview, observation and documentation methods. The sample is 10 mustahiq recipients of productive zakat and 5 mustahiq recipients of consumptive zakat. While the method of determining the sample is by means of purposive sampling. The data analysis technique was carried out with an inductive model consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show: 1. The management of Baznas in Sambas Regency has not been optimal in planning, organizing, implementing, and supervising. 2. The level of public confidence in the performance of Baznas in Sambas Regency is still low. 3. There is an increase in the standard of living of the mustahiq, and the level of welfare of the mustahiq is classified as pre-prosperous. In this case it is necessary to hold training to form competent human resources, there is a need for a mentoring program for mustahiq recipients of productive zakat, there is a need for supervision in managing zakat, infaq and shadaqah funds.